English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

For what value of b in the equation 2x + 3b – 3 = 4x – 3b will the solution for x be 3?

2007-07-04 11:19:27 · 7 answers · asked by wizzdom13 1 in Science & Mathematics Mathematics

7 answers

Substitute x = 3 in the equation

2*3 + 3b – 3 = 4*3 – 3b
6 + 3b – 3 = 12 – 3b
6b = 9
b = 3/2

2007-07-04 11:24:40 · answer #1 · answered by psbhowmick 6 · 2 2

2x + 3b - 3 = 4x - 3b
For x = 3
2(3) + 3b - 3 = 4(3) - 3b
6 + 3b - 3 = 12 - 3b
3b + 3 = 12 - 3b
6b = 9
b = 9/6
b = 3/2 or 1.5

2007-07-04 18:34:35 · answer #2 · answered by Dude2001 2 · 0 0

2x +3b - 3 = 4x - 3b
0 + 6b - 3 = 4x -2x
6b - 3 = 2 x

So
b = (2x +3)/6

If x = 3,
b = (6+3)/6 = 9/6 = 3/2

b = 3/2

2007-07-04 18:56:18 · answer #3 · answered by ? 6 · 0 0

Substitute x = 3

6 + 3b - 3 = 12 - 3b

6b = 9

b = 1.5

2007-07-04 18:25:33 · answer #4 · answered by Twiggy 7 · 0 4

3/2

2007-07-04 18:25:45 · answer #5 · answered by UNIQUE 3 · 0 3

2x + 3b – 3 = 4x – 3b
2x = 6b-3
If x = 3 , then 6=6b-3 --> 6b=9 --> b=3/2

2007-07-04 18:25:52 · answer #6 · answered by ironduke8159 7 · 0 4

"b" has to equal 1.5 or 3/2

2007-07-04 18:27:38 · answer #7 · answered by Anonymous · 0 3

fedest.com, questions and answers